On-chip orbital angular momentum sorter for demultiplexing based on arc-shaped waveguide grating. (December 2022) - Wang, Zixiao; Sun, Chunran; Xiao, Shiying; Wu, Beilei; Jiang, Youchao
Highlights: An arc-shaped waveguide grating structure is proposed and optimized for selective coupling of vortex beams. Extinction ration of the proposed orbital angular momentum sorter is higher than 8.19 dB from 1530 nm to 1570 nm. The proposed orbital angular momentum sorter is scalable, and parameters of the sorter can be adjusted to fit various sorting demands. Abstract: An on-chip orbital angular momentum (OAM) sorter based on the arc-shaped waveguide grating coupler (AWGC) structure is proposed and numerically analyzed. Coupling characteristics of the AWGC are discussed in detailed. Utilizing the phase matching mechanism of the AWGC, unidirectional-propagation guided modes can be excited by vortex beams possessing specific topological charge. By combing multiple AWGCs having different parameters, the on-chip OAM sorter is constructed. Performance of OAM sorting and demultiplexing are investigated with the results confirming the high extinction ratio and low crosstalk on each output port within the C-band. The proposed structure is expected to find potential applications in OAM demultiplexing.